1979
DOI: 10.1016/0035-9203(79)90209-8
|View full text |Cite
|
Sign up to set email alerts
|

The pathology and pathogenesis of fatal hepatic amoebiasis—a study based on 79 autopsy cases

Abstract: The present study is based on a retrospective analysis of 79 autopsy cases of hepatic amoebiasis. An attempt has been made to reconstruct the sequence of events starting from intestinal infection to invasion and transport of amoebae along the radicles of the portal veins, the formation of early Zahn's infarct and the proliferation of amoebae in such foci leading to the formation of small abscesses. The coalescence of small abscesses gives rise to the apparently large abscesses. Apart from direct contiguity, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 5 publications
2
23
1
Order By: Relevance
“…The mechanisms of damage caused by the E. histolytica in the mucosa of the colon of FAC patients are similar to those described in liver with invasive amebiasis (Aikat, 1979;VenturaJuárez, 1997). It has been seen that when E. histolytica are present, tissue damage can be caused by E. histolytica adhesion, lysis of host cells, and effects of the proteolytic enzymes derived from the parasite (Huston, 2004;Stanley & Reed, 2001).…”
Section: Role Of the Cellular Immune Responsesupporting
confidence: 66%
“…The mechanisms of damage caused by the E. histolytica in the mucosa of the colon of FAC patients are similar to those described in liver with invasive amebiasis (Aikat, 1979;VenturaJuárez, 1997). It has been seen that when E. histolytica are present, tissue damage can be caused by E. histolytica adhesion, lysis of host cells, and effects of the proteolytic enzymes derived from the parasite (Huston, 2004;Stanley & Reed, 2001).…”
Section: Role Of the Cellular Immune Responsesupporting
confidence: 66%
“…Although brisk neutrophilic infiltration characterizes early amebic invasion, human autopsy studies have revealed very little reactive inflammation surrounding chronic amebic liver abscesses, and a similar paucity of inflammation has been noted at the base of well-formed colonic ulcers (1,8,19,36). We hypothesize that the rapid clearance of apoptotically killed cells by amebae (and perhaps also by tissue macrophages) limits the leakage of toxic intracellular contents of killed cells.…”
Section: Discussionmentioning
confidence: 94%
“…Entamoeba histolytica, the protozoan parasite that causes amebic colitis and liver abscesses, is characterized clinically by its ability to cause indolent infection and pathologically by only moderate inflammation during chronic infection, despite extraordinary tissue destruction (1,6,19,20). Amebic cytotoxicity and phagocytic ability both correlate with parasite virulence (21,23,24,26,31,35).…”
mentioning
confidence: 99%
“…However, a study based on autopsy cases reported that 27.5% of portal veins, 29.5% of hepatic veins, and 4% of inferior vena cava were thrombosed. 5 These thromboses were caused by either compression of the inferior vena cava or the portal or hepatic veins. The diagnosis of Budd-Chiari syndrome should be considered in a clinical manifestation of prolonged fever unresponsive to treatment for amebiasis or ascites associated with bilateral lower limb edema and collateral abdominal venous circulation.…”
mentioning
confidence: 99%